Konsep Kecerdasan Emosional dalam Relasi Suami Istri: Telaah Terhadap Makna Al-Libas QS. Al-Baqarah Ayat 187 - Serly Tiara Amani Zulfa; Ahmad Nurrohim (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study aims to examine the metaphorical meaning of al-libas in QS. al-Baqarah verse 187 and integrate it with the concept of emotional intelligencein the context of husband-wife relationships. This study uses aqualitative approach based on library research withthematic interpretation methods and an interdisciplinary approach between Al-Qur'aninterpretation and modern psychology. The primary data sources are from the Qur'an and classical and contemporary tafsir books, while the secondary data are in the form of psychology literatureand studies on family relationships. The results showthat al-libas has a symbolic meaning that includes protection, tranquility, and beauty in husband-wife relationships. These valuesare consistent with the main components of emotional intelligence according to Goleman, namely self-awareness, self-regulation, and empathy. The integration of the twogives rise to a “Qur'anic-emotional relationship” paradigm that emphasizes the balancebetween spiritual maturity and emotional maturity in the household. The implications of this study indicate that understanding the meaning of al-libascan serve as a conceptual and practical basis for fostering a harmonious Islamic family, while enriching the wealth of contextual and applicative interpretations inaddressing modern human relationship problems.